On the Timing and Pricing of Dividends: Comment - Schulz, Florian (American Economic Review, 2016)
I present novel empirical evidence on the term structure of the equity risk premium. In contrast to previous research that documented high discount rates for the short-term component of the market portfolio, I show evidence for an unconditionally flat term structure of equity risk premia. The tension with previous literature arises largely as a result of differential treatments of heterogeneous investment taxes, manifested in micro evidence on abnormal equity returns on ex-dividend days, and liquidity. The results not only help resolve an important recent “puzzle” but provide further important insights on the role of investment taxes in asset pricing. (JEL G11, G12, G35)